Assessment of Reinforced Concrete Columns Using Ultrasonic Tomography - Alexandre Lorenzi; Leonardo Covatti de OLIVEIRA; Tobias Pigatto Ottoni; Lucas Alexandre Reginatto; Luciani Somensi Lorenzi (e-Journal of Nondestructive Testing)
Nondestructive testing (NDT) is increasingly being used in the construction industry for auxiliary inspection of concrete structures. One of the most used techniques is the measurement of the ultrasonic pulse velocity. In this paper, five reinforced concrete pillars were inspected using the ultrasonic echo of shear waves to create a cross-section tomography of the pillars. A 10 cm x 10 cm grid was used, amounting to 600 measurements. Observing a heterogeneity of the echo pulse velocities was possible, indicating possible pathological manifestations in the structural elements. The data collected generated a 3D image of the reflected interfaces of the component. The present article illustrates the application of ultrasonic tomography (UT) in evaluating the conservation state of reinforced concrete pillars.